The The NewConnect market as a source of raising funds for the SMEs - Zabielska, Izabela; Ejsmont, Aneta (Ekonomia i Prawo. Economics and Law, 2023)
Motivation: The NweConnect market is intended for small, innovative and dynamically developing companies, especially in the so-called new economy. A debut on this market is one of the possible strategies for raising capital by a small and medium-sized entrepreneur. In times of economic downturn and limited supply of capital on the capital market, only the most credible have a chance to raise capital on the alternative market. Aim: recognition of the actual nature of companies listed on the alternative market in Poland, with particular emphasis on the voivodeships of Eastern Poland. It was assumed that mainly young, innovative and fast-growing companies are listed on the NewConnect market. The analysis was based on a review of domestic and foreign literature and on the estimated linear econometric model. Results: Most companies on the NewConnect market are not characterized by rapid development, short period of entering the market and a high level of innovation. There are also companies from industries where the level of innovation was not a key element of activity from the beginning. In addition, the changes that have taken place (i.e. from market entry to the current situation, 2007–2022) are not favourable. While at the beginning of their activity (since 2007) listed companies were characterized by a relatively high level of innovation, now (2022) this level is decreasing. This justifies the need for further research on the development of the NewConnect market as a source of financing for small and medium-sized enterprises.